Effect of adding milk to a micronutrient fortified high-energy biscuit school feeding programme in Yemen: A cluster-randomised controlled trial - Bliznashka, Lilia; Michail, Monica George; Elsabbagh, Dalia; Gelli, Aulo; Hamid Hossam Al-Qadi, Ahmed Abdel; Saif Al-Ariqi, Munir Hassan; Hanash Qasim, Wajdan Hanash; Qawi Al-Athouri, Saeed Abdul; Hamid Ahmed Abdullah, Majed Abdel; Ali Naji Iskandar, Samia Majed; Hamoud Al-Battah, Nazma Saleh; Hamid Mansour, Salah Fazaa; et al. (Elsevier, 2025)
Background Two billion children globally are estimated to live in conflict-affected areas. School feeding programmes (SFPs) are a widely implemented safety net that supports children during and after conflict.